Histopathological and ultrastructural characterization of equine hoof shape deformities - Al-Agele, Ramzi (2018)
Satisfactory investigations of the equine foot appear to be limited by the histo-morphological complexity of internal hoof structures. Foot lameness is considered to be one of the most debilitating pathological diseases in the horse. In most species, foot lameness is traditionally linked to hoof deformity, and a set of molecular events have been defined in relation to the disease. The differential capsular growth rate is essential in order to understand the aetiology of hoof distortions. It is now well established that keratinocyte progenitor cells grow from the papillae and not from the lamellae. The importance of hoof material synthesis, and therefore the underlying cell proliferation from the papillae, in the pathology of laminitis has been underlined in different species. Despite this knowledge, it remains unclear how cell proliferation itself is involved in this pathology. So far, there is controversy regarding the incidence of foot lameness in horses, as it is unclear whether it is foot lameness that triggers hoof distortions or vice-versa. In addition, very little scientific evidence exists to prove either point; this requires a deeper understanding of the physical biology and biomechanics of the hoof given that the horse stands on its hooves. It is remarkable that very little physics has been introduced to enhance our understanding of the disease. In order to develop a better understanding of foot lameness, we aim to provide a model of foot lameness encompassing anatomy, cell biology and physics to help reveal new evidence for evaluating the incidence of pathological changes within internal structures of the animal’s foot. It is anticipated that the results found will aid in bridging this gap in knowledge. Fifty-four equine hooves were collected and categorized based upon their morphology, and tissue sections were harvested from the periople, coronary and proximal part of lamellae. Markers of progenecity (p63), cell proliferation (PCNA, Ki-67) and differentiation (K14, K10) were used to assess the hoof growth rate in coronary regions using immunohistochemistry (PCNA, Ki-67, p63) and immunofluorescence (p63 and K14). For assessing the involvement of physical forces in hoof growth, the Micro CT-scans of individual foot were analysed to highlight differences in the ultrastructure of the feet, for example differences in dorsal curvature between different foot samples. The results presented in this study confirm previous findings, add evidence that a high percentage of Ki-67 and p63 positive cells are found in the proximal part of the papillae, and seem to contribute to hoof deformities. This evidence might be attributed to physical growth forces present in the proximal part of the hoof whereby the change in cell size might contribute to force generation, tissue remodelling (i.e. cornification) and hoof deformities. As hoof distortion can result from uncontrolled epidermal basal cell proliferation from the epidermal papillae. A model of cultured keratinocytes under different stresses such as stretch, hydrostatic pressure and/or low oxygen conditions. This revealed that these stresses together with low oxygen conditions stimulate cell differentiation, and upregulate keratin levels. Consequently, this leading to changes in their morphology and cell surface area. Together these results suggests that cell culture, growth, passage and physical or biological treatments have improved our knowledge of natural cell stimulation and aid our understanding of how equine progenitor keratinocytes (EPKs) would hypothetically respond to external stimuli other than biological ones. The results presented regarding physical forces showed that there is a strong correlation between the dorsal hoof curvature and the level of Ki-67 and p63 abundance at the dermal papillae. In addition, K14 and TUNEL apoptotic cells localized along the dermal papillae in the coronary hoof region were also found in ‘dished’ hooves. Specifically, when the hoof curvature is positive (i.e. for the ‘dished’ hoof) there is an increase in the mitotic index shown by Ki-67 and p63 expression in the quarter regions compared to the dorsal one. Negative hoof curvatures (i.e. having a claw-like shape), however, did not shown any correlation with Ki-67 and p63 expression in any tissue type, except for K14 expression levels in the dorsal and quarter regions. These outcomes demonstrated that the two proteins (p63 and Ki-67) participate in hoof growth, and very probably to the differential growth of the hoof capsule as observed in chronic laminitis. This is probably through a contribution of sustained level of epidermal basal cell proliferation. In conclusion, the morphometric data of the change in cell size and the localisation of proliferation cells on the proximal part of papillae provide evidence on the way of hoof morphogenesis. These were confirmed with behaviour of cultured keratinocytes under different stresses. Additionally, the difference in the proliferation rates between the dorsal, quarter regions of the hoof wall are connected to hoof curvatures. The data gives new insights into the physical biology of the normal versus pathologically affected equine feet, and bovine and ovine feet in the future, providing new information for potential treatment(s). Consequently, this research aims to bridge gaps across scientific fields to ameliorate our understanding of the equine foot. However, further studies need to be carried out in order to understand the pathways of cellular response at the coronary region.